Elevation [compact disc, unabridged] - King, Stephen, 1947- (Audioworks, Simon & Schuster Audio, 2018)
A timely tale about the power of finding common ground traces the story of Scott Carey, whose mysterious affliction unites the small community of Castle Rock, Maine.